Optimization of Impact and Thermal Performance of Phenolic Composites through Bentonite Reinforcement - Gojandra, Farda Pega Libra; Priyanto, Kaleb; Kurniadi, Ninda (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
This study aims to determine the effect of the addition of montmorillonite bentonite powder on the mechanical properties and burn resistance of phenolic resin-based composites. Composite samples were made with variations in bentonite weight fractions of 0%, 5%, 10%, and 15%. The impact test was carried out using the Izod method to determine the energy absorption and impact price, while the burn resistance was tested based on the ASTM D635 standard to determine the Time of Burning (TOB) and the Rate of Burning (ROB). The test results showed that the addition of bentonite lowered the impact price, with the highest value of 0.0082 J/mm² in the 0% fraction and the lowest of 0.0008 J/mm² in the 5% fraction. The highest absorption energy is obtained in the 10% fraction of 0.145 J. This decrease in mechanical performance is influenced by the inhomogeneous distribution of the catalyst and the presence of voids in the composite structure. In contrast, the addition of bentonite provides a significant increase in burn resistance. Composites with a fraction of 15% show the highest TOB of 20 seconds and the lowest ROB of 9.4 mm/min, indicating increased flame resistance. The mineral content of montmorillonite in bentonites, such as silica and alumina, contributes to slowing down the rate of combustion through increased material density and stable thermal properties. The results of this study show that montmorillonite bentonite powder has the potential to be used as a flame retardant additive in composite materials, but it needs to be studied further to maintain a balance between fire resistance and mechanical strength.